Peer Reviewers of JMH Volume 1 Number 2 - Medicine; Health, Journal of (Maranatha Christian University, 2015)
We would like to thank our peer reviewers for the precious contributions in providing clinical,scientific, and methodological expertise for JMH Volume 1 Number 2. We appreciate everythoughtful review of submitted manuscripts and for making important contributions to improve thescientific quality of articles published in JMH. We listed the names in alphabetical order.Dr. dr Diana Krisanti Jasaputra, M.Kesdr. Djaja Rusmana, M.Si.Dra Endang Evacuasiany, M.S, AFKdr. Fenny, Sp.PKDr. dr. Hana Ratnawati, M.Kes., PA(K)Prof. Dr. Ida Parwati, dr, SpPK(K), PhDdr. Indra Sapta, Sp.THT-KLIngrid S. Surono, PhD.Dr. dr. Meilinah Hidayat, M.Kesdrg. Monica Irewaty Wibisana, M.Kes Sert Ortdr Sijani Prahastuti,M.Kesdrg.Susiana,Sp.OrtProf. Drs. Sutiman B.Sumitro,SU.,D.ScSylvia Soeng, dr., M.Kes., PA(K)Dr. Teresa Liliana W, S.Si., M.Kes., PA(K)Prof. dr. Wahyuni Lukita Atmadja, PhD.Dr. Yudi Mulyana H.,dr.,SpOG(K)